An introduction to the economic theory of market behavior : microeconomics from a Walrasian perspective - Katzner, Donald W.; Katzner, Donald W. (Cheltenham, UK Northampton, MA : E. Elgar, 2006)
This is an important, rigorous, and engaging text on the economic theoryof market behavior. It is unique in the attention devoted to the philosophical underpinnings and the historical background of the Walrasian Theory.
Rev. ed. of: Walrasian microeconomics. c1988.
Includes bibliographical references and index.
osc 13/02/14.
Loans
Keywords: Microeconomics; Economics, Mathematical; Capitalism